Assessment of Risk Factors for Cardiovascular Complications in Patients with Chronic Kidney Disease (CKD) Stage III-V before Dialysis - Khan, MK; Rashid, HU; Yesmine, S; Mahmoo, IH; Habib, SMA; Hossain, A (University Heart Journal, 2014)
Background: Chronic Kidney Disease is a major public health and clinical problem throughout the world including Bangladesh. The prevalence of cardiovascular complications is much higher in patients with CKD regardless of stages than normal population. Considering this view, a cross sectional study was conducted in the Department of Nephrology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, with an aim to assessing the cardiovascular complications & associated risk factors among the patients with chronic kidney disease (CKD) stage III-V before dialysis. Methods: A total of 109 patients were selected consecutively who had a diagnosis of CKD and an estimated GFR of less than 60 ml/min/1.73m2 of stages III to V and who had not received any form of renal replacement therapy, during a period of June 2006 to July 2007. Results: The study included 63 males and 46 females with age ranging from 18 to 65 years having a mean age 45.5±12.2 years. Left ventricular failure, left ventricular hypertrophy (by ECG and echocardiography), cardiomegally by X-ray were identified as significant cardiovascular complications among the patients of CKD stage V (p<0.05). However , logistic regression analysis revealed that hypertension and CKD stages appeared to be the important predictors of cardiovascular complications p<0.05). Data analysis found that hypertension, smoking and anemia appeared to be important risk factors for cardiovascular complications in CKD patients (p<0.05) by bi-variate analysis. Conclusion: Though the study findings did not generalize the CKD patients in Bangladesh due to small sample size, however, heart failure and left ventricular hypertrophy significantly appeared to be the main cardiovascular complications in CKD stage V compared to other two stages (stage III and IV)(p<0.05). Anemia, hypertension were identified as important risk factors (p<0.05). DOI: http://dx.doi.org/10.3329/uhj.v9i1.19508 University Heart Journal Vol. 9, No. 1, January 2013; 25-32